Semisupervised Semantic Segmentation With Certainty-Aware Consistency Training for Remote Sensing Imagery - Yongjie Guo; Feng Wang; Yuming Xiang; Hongjian You (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2023)
Semisupervised learning is a forcible method to lessen the cost of annotation for remote sensing semantic segmentation tasks. Recent related research works indicate that consistency training is one of the most effective strategies in semisupervised learning. The core of consistency training is maintaining model outputs consistent under various perturbations. However, the current consistency training-based semisupervised semantic segmentation frameworks lack the analysis of model uncertainty, which increases the generation of semantic ambiguity on remote sensing images. Therefore, we propose the certainty-aware consistency training (CACT) strategy to mitigate the influence of semantic ambiguity caused by model uncertainty. The CACT strategy consists of two novel parts: certainty-aware consistency correction (CACC) and class-balanced-adaptive threshold (CBAT) strategy. The CACC starts with generating a high-quality prediction target, then models the importance of the consistent output target and corrects the output predictions according to the certainty map, increasing the focus on reliable predictions. The CBAT strategy uses a dynamic class-balanced adaptive threshold to filter out unreliable predictions, further reducing the impact of semantic ambiguity. Finally, considerable experimental results on the DLRSD, WHDLD, and Potsdam demonstrate that our framework has an excellent performance on semisupervised remote sensing semantic segmentation scenarios.